Parents' encounters with 'the sexualisation of childhood': paying attention differently?. Issue 4 (19th May 2021) - Kitching, Karl; Kiely, Elizabeth; Ging, Debbie; Leane, Máire
ABSTRACT: This paper draws on an Irish government-commissioned study of parents' views about the sexualisation and commercialisation of children. We examine how parents understand 'sexualisation' qualitatively, through their evoking of past, present and future images of childhood. The data underlines how sexualisation becomes rationalised as something to protect against and control, not least through the restrictive surveillance of girls' development. But we use the concept of duration to analyse various, differing ways images childhood endure in parents' experience. This leads us to argue parents' relations to images of childhood complicate, rather than solely reproduce, discursive understandings of sexualisation as a unitary phenomenon threatening 'normal' child development. We contend that further mapping of the ways images of childhood endure in parents' experience may help refuse their impossible positioning as guardians of child innocence, and generate more complex forms of attention to sexualisation, which challenge gendered and heteronormative societal assumptions about children's development.